The Role of Agricultural Extensioners in the Development of Tomato Farming in the Neighborhood of Folarora City of Tidore Islands - Dodi Alfair M.Abhar; Nur Azizah HS; Maman Abdulrachman; Muhammad Julham (International Journal of Education, Information Technology, and Others, 2023)
The agricultural sector plays an important role in the Indonesian economy. One of the potential agricultural sectors to be developed is tomato cultivation. The development of the productivity of tomato farming in Folarora Village requires the support of quality human resources through agricultural extension. The existence of tomato farmers is inseparable from the role of agricultural extension workers who are at BPP (Agricultural Extension Center) Tidore Islands City which aims to improve tomato farming. The purpose of this study was to determine the function of the motivator carried out by extension agents for the development of tomato farming, to know the function of the facilitator carried out by extension agents for the development of tomato farming and to find out the function of mediators carried out by extension agents for the development of tomato farming. The research methodology used is descriptive qualitative research. Data uses two types of data sources, namely primary data and secondary data. Data collection techniques in this study were observation, structured and unstructured interviews and secondary data tracking. The data analysis techniques used in this study were data reduction (data editing), data display (data presentation) and conclusion drawing / verification. The results showed that the role of extension agents as a motivator includes motivation in increasing the development of tomato farming, motivation in increasing profits, motivation in solving the problems encountered. The role of extension workers is as a facilitator in fulfilling the advice and infrastructure of tomato farming, facilitating tomato farming farmers to form farmer groups or form agricultural cooperatives consisting of these farmers. The role of the extension worker as a mediator connects or serves farmers with the government.